The Positive Effect of Psychotherapy in the Treatment of an Erosive Oral and Dermal Lichen Planus Case - Zana Fuad Noori; Mohammed Khalid Mahmood; Pinar Yaseen Raof; Handren Ameer Kurda; Balen Hamid Qadir; Didar Anwar Abdulrahman; Mohammed Aso Abdulghafor; Mohammed Taib Fatih; Basoz Khalid Hama Noori (Clinical Case Reports)
ABSTRACT Lichen planus (LP) is an autoimmune disease that may affect the oral cavity and the skin, and it has the potential to change to malignancy. In this paper we report a LP case in a 42‐year‐old male patient in which anxiety and depression were apparently the only possible risk factors of LP. Due to this apparent comorbidity and the risk of not responding well to conventional medication (topical and systemic corticosteroids) or the risk of relapse in the case of ongoing stress, we decided to integrate psychotherapy (without psychotropic drugs) as an adjunct into the management strategy. Psychotherapy sessions, reassuring the patient and stress alleviation, proved to be a very useful alongside the standard corticosteroid medication.